Association of 24-Hour blood pressure average real variability with poor prognosis in critically ill patients with coronary artery disease - Peng-fei Sun; Yan Chen; Yu-Qin Zhan; Pan-pan Shen; Chen-yang Wu; Yu-bin Shen; Ya-hui Ding (Scientific Reports)
Abstract Despite advancements in treatment, the overall mortality rate among critically ill coronary artery disease (CAD) patients remains high. The impact of blood pressure variability (BPV) on these patients remains controversial. This study investigates the relationship between 24-hour BPV and mortality in critically ill CAD patients in the ICU. A retrospective analysis was conducted on CAD patients admitted to the ICU from 2008 to 2019 using the MIMIC-IV database. BPV was assessed by calculating average real variability (ARV) during the first 24 h of ICU admission, classifying patients into low, medium, and high ARV groups. Endpoints included in-hospital and 1-year mortality, analyzed using logistic regression, Cox proportional hazards regression, and restricted cubic splines. A total of 4,588 CAD patients were included. ARV of diastolic blood pressure (DBP) was positively correlated with 1-year mortality (HR 1.03, 95% CI 1.00-1.06), independent of other factors. ARVof systolic blood pressure (SBP) showed a U-shaped relationship with 1-year mortality; values below 16.912 mmHg reduced risk (HR 0.956, 95% CI 0.924–0.988), while higher values increased risk (HR 1.180, 95% CI 1.044–1.333). No significant associations were found with short-term mortality. In critically ill CAD patients, 24-hour ARV of DBP and SBP show significant associations with 1-year mortality. Elevated DBP variability is associated with increased risk, while SBP variability demonstrates a U-shaped association, suggesting both very low and very high SBP variability are detrimental. These findings highlight the potential importance of monitoring BPV to identify high-risk patients and suggest that targeted BP management strategies, considering variability, may improve long-term outcomes.